Use of Design Theories and Principles in Visual Brand Identity Elements in Commercial and Retail Banks - Donia Bettaieb; Abeer Alsobahi (ITB Journal Publisher, LPPM ITB, 2022)
Studies on the processes that link logos and space design aesthetics to visual perception and recognition of visual brand identity (VBI) remain scant. Consequently, this study analyzed the visual correspondence between visual brand identity elements such as logos and interior spaces in commercial retail banking companies by assessing the foundations of their aesthetics formation and the role of aesthetic principles, aesthetic appraisal, and aesthetic impression. Using a qualitative approach, four commercial retail banking companies in Jeddah, Saudi Arabia were analyzed through semi-structured interviews with professional designers and design academics. A comparative method was used to determine the visual correspondence between the aesthetics of the logos and the interior spaces. The findings confirmed the importance of using design characteristics and theories for designing the elements of VBI. The results encourage the use of design for building visual correspondence between the elements of a visual identity of brands. This study provides a useful addition to knowledge on the place of design principles in the creation of VBI.